Development and validation of a questionnaire on tuberculosis among foreign-born individuals in a province of northern Italy - Mariachiara Di Nuzzo; Giorgia Valpiani; Chiara Morotti; Martina Maritati; Carlo Contini (Journal of Infection in Developing Countries)
Introduction: In low tuberculosis (TB) incidence countries, foreign-born individuals represent a population at risk. Knowledge, Attitude and Practice (KAP) surveys use standardized and structured questionnaires to collect information by a specific population in relation to a particular topic. As primary objective, we developed and validated a questionnaire exploring TB knowledge among foreign-born individuals from high TB incidence countries living in Ferrara’s province, a low TB incidence province of northern Italy. As secondary objective, we investigated respondents’ demographic and social determinants of health data. Methodology: Questionnaire items were developed based on World Health Organization (WHO) “A guide to develop KAP surveys” questionnaire sample and literature review. Questionnaire underwent Delphi technique evaluation, back and forward translation, health literacy review, and two pilot tests. Internal consitency and validity were computed through Cronbach’s alpha, content validity index, and principal component analysis (PCA). Descriptive statistics were used to summarize demographic and social determinants of health data. Results: We initially proposed a 38-item questionnaire. After Delphi technique, performed with seven experts, a 17-items questionnaire was obtained. Cronbach’s alpha coefficient, used to assess internal consistency, was 0.65. Content validity index was > 0.80. One factor was extracted by PCA, with a cumulative contribution of 50%. The population investigated was similar to the immigrant population settled in Ferrara’s province, according to age, gender and TB risk factors. Conclusions: The questionnaire we developed and validated can contribute to measure foreign-born individuals’ TB knowledge.